Simple,its just like this: 6x+1+7-3 =6x+8-3 =6x+5
3x + 8
9x2+6x-7 = 0 Using the quadratic equation formula:- x = 0.6094757082 or x = -1.276142375
Without an equality sign it can't be considered to be an equation
-6x^2 - 78x - 252 Improved answer: -6x+6x+7 When simplified = 7
Simple,its just like this: 6x+1+7-3 =6x+8-3 =6x+5
It is an expression that can be simplified to: 6x+1
Without an equality sign the given expression can't be considered to be an equation and so therefore no solution is possible.
4
3x + 8
9x2+6x-7 = 0 Using the quadratic equation formula:- x = 0.6094757082 or x = -1.276142375
Without an equality sign it can't be considered to be an equation
Combine like terms. 6x - 2y +7.
No, it is an expression.
A quadratic equation. If you wish to solve for x, you can do so as follows: -x2 + 6x + 7 = 0 x2 - 6x - 7 = 0 (x - 7)(x + 1) = 0 x ∈ {-1, 7}
-6x^2 - 78x - 252 Improved answer: -6x+6x+7 When simplified = 7
-1